Tipo assim...ser aluno adolescente no IFES Campus Colatina : sentimentos e impressões - Ferrari, Marlinda Gomes (2013)
This research aims to present, from the students’ perspective, what it means to be a student in IFES, what are the feelings about themselves, about their pairs, about their family and how do the relations between teacher/student/subject of knowledge happen. The theorical reference adopted in this research was based on the researches of Vigotski and Wallon, who emphasized the historical-cultural perspective and consider that affective and cognitive dimensions interlace in the individual. The methodology used was the case study, insert in the scope of research of qualitative approach. The gathering of data was made through documental analyses and private interviews with twenty 14 to 18 years-old juvenile students, matriculated in the Building Technician Course Integrated to Ensino Médio of IFES campus Colatina-ES. The analysis, on the other hand, is made by grouping of thematic categories, such as: Teachers and Pedagogical practice, Feelings about themselves, Relation with colleagues, Relationship with the family and about being an IFES student. The results pointed to the importance of considering the adolescent as a person who is constituted through the relation with the other and to the fact that the quality of this relation affects his both affective as cognitive dimensions, interfering in school, in his efficiency and his relationship with the others, according to the way each person receives and react to daily situations. They also point to the necessity of the teacher to know the specific features of that age, looking for different methodologies to wake up the student’s interest to the knowledge object. In this research, is clear the much young students need someone to hear them, to know who they are, what affected/affect them and how their life experience contributed/contribute to the constitution of their own being